Embedding laboratory animal welfare- and ethics-related techniques into a comparative medicine laboratory course: an educational reform study - Jian Zhang; Lingyan Zhang; Xingtao Zhang; Gang Yao (Frontiers in Veterinary Science, 2026)
Background Animal welfare and ethics education is essential for laboratory animal science training, but students often struggle to translate ethical principles into practical experimental procedures. This study explored an embedded teaching approach that integrated animal welfare- and ethics-related techniques into a comparative medicine laboratory course using the bilateral ovariectomy (OVX) mouse model as an authentic teaching scenario. Methods A pre–post educational intervention design was adopted. Students first independently wrote welfare- and ethics-related technical plans for the OVX experiment. Instructors then provided structured teaching covering model justification, anesthesia and analgesia, perioperative care, postoperative monitoring, humane endpoints, sample collection, euthanasia, welfare recording, and institutional compliance. After instruction, students revised their plans using the same assessment criteria and subsequently performed OVX procedures under instructor supervision. Their technical standardization and welfare-related performance were evaluated using a predefined practical rubric. A post-course questionnaire was used to assess students’ perceptions of the teaching model. Results After instructor explanation, students’ correct response rates improved across all assessed welfare domains, particularly in model justification, surgical procedures, analgesia, welfare recording, and intervention strategies. In the practical assessment, 80 students achieved a mean score of 81.96 ± 5.86, with a median score of 83.00; 65.0% scored 80 or above, and no student scored below 70. Post-course questionnaire results showed strong acceptance of the embedded teaching model, with all dimensional mean scores exceeding 4.40 on a 5-point Likert scale. The highest scores were observed for attitude and ethical awareness, overall evaluation, and OVX scenario-based learning effect. However, score-loss analysis and questionnaire findings revealed remaining weaknesses in anesthesia depth monitoring, analgesia implementation, intraoperative welfare protection, postoperative observation, welfare documentation, and humane endpoint-related decision-making. Conclusion Embedding animal welfare- and ethics-related techniques into OVX-based experimental teaching was associated with improvements in students’ understanding, attitudes, and practical application of welfare-related procedures. This approach may help students progress from abstract ethical awareness to practical ethical competence and provides a feasible framework for animal welfare and ethics education in laboratory animal science programs.